PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PADA HUSH DIVISI BAZAR CABANG TANGERANG - Lazuardi, Tazqia Nabila; Susanti, Fahmi; Putri, Laila Listiani; Hapiyudi, Salman (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to examine the influence of Reward and Punishment on Employee Performance at Hush Bazaar Division, Tangerang Branch. This study uses a quantitative approach with associative analysis. This study uses field observation techniques by distributing questionnaires to 60 employees at Hush Bazaar Division, which includes area coordinators and sales officers. The measurement scale uses Ordinal 'Likert'. The data analysis technique in this study was carried out through several stages, namely validity testing, reliability testing,coefficient of determination (R2) testing, and hypothesis testing. The Reward variable was not proven to have a significant effect on Employee Performance. Then, the Punishment variable was proven to have a significant effect on Employee Performance, while both, namely the Reward and Punishment variables, were proven to have a simultaneous effect on Employee Performance at Hush Bazaar Division, Tangerang Branch, and contributed 46.8 percent